Performance analysis of direct QPSK modulator - Hafizah Zainal Abidin
The objective of this final year project is to design direct QPSK modulator which can operate at 2.4 GHz. The scope of this project is to study the QPSK modulator and analysis the performance of direct QPSK modulator. The IC used to design QPSK modulator is MAX 2721.